Relational Views of Humanness: The Reciprocity of Ontos and Telos. (May 2020) - Pally, Marcia
This article explores humanity's ontology of relationality and telos of the common good as not only inseparable but mutually constitutive, drawing on the work of Thomas Aquinas and looking into the debates between Charles De Koninck and Jacques Maritain.